Soil physical properties of a Luvisol developed on loess after 15 years of amendment with compost - Paradelo, Remigio; Eden, Marie; Martínez, Ingrid; Keller, Thomas; Houot, Sabine (Soil & tillage research, 2019)
•We studied the impact of organic amendments on the physical properties of a Luvisol.•After 15 years, compost and manure increased water retention and the Atterberg limits.•Compost and manure amendments increased air permeability and gas diffusivity.•The amendments improved soil physical conditions for tillage and agricultural operations. Recycling composted organic residues in agriculture can reduce the need for mineral fertilizers and improve the physicochemical and biological properties of cultivated soils. However, more studies dealing with soil physical properties after compost amendment are still needed. The objective of this study was to investigate the impact of long-term compost amendment on soil physical properties in a silt loam Luvisol under a maize-wheat rotation in the Paris Basin. Since 1998, three composts and one manure were applied every second year after wheat harvest, at a rate of ca. 4 Mg C ha−1. Bulk density, organic carbon concentration on a mass basis, water holding capacity, gas transport properties and Atterberg limits were measured on topsoil samples taken 15 years after the beginning of the experiment. Soil moisture was monitored in the field down to a depth of 160 cm during two years with different climatic conditions: a year with a dry summer (2010) and a year with a wet summer (2012). Compost and manure amendments reduced bulk density and increased organic carbon concentrations, which improved apparent air permeability and gas diffusivity, but only one of the amendments (a green waste-sewage sludge compost) increased water-holding capacity. The amendments also increased the water contents at the Atterberg limits and overall produced better soil conditions for tillage and other agricultural operations, in particular in wet years. However, field moisture measurements showed that in general, soil water contents were not higher in the amended soils than in the control at any of the periods considered.